Laser-induced autofluorescence and decay dynamics of human colonic tissues - Huang, Zhiwei. (2008)
This thesis reports investigations of light propagation in the tissue by Monte Carlo modelling, laser-induced autofluorescence (LIAF) spectroscopy and dynamics of autofluorescence decay in normal and tumour human colonic tissues. Two instrumentation systems were developed to advance this research. A theoretical model was developed to further improve the understanding of macroscopic spectroscopic measurements.